Perceived playfulness, perceived usefulness, confirmation dan continuance intention pada layanan video on demand: satisfaction sebagai mediasi - Roberto Andrew; Retno Ardianti (MBR (Management and Business Review), 2022)
Despite the increasing number of video-on-demand (VOD) subscribers during the pandemic, extant research has not explained factors that might contribute to customers’ intention to continue their subscriptions. Therefore, this study aims to explain the effect of perceived playfulness, perceived usefulness, and confirmation on continuance intention with satisfaction as the mediating variable. By using partial least squares (PLS) in our data analysis, our results show the importance of confirmation or the fit between customer expectations and their real experiences in using VOD services on continuance intention. In addition, the results show the role of customer satisfaction either as the full mediating or partial mediating variable that explains the relationship between perceived playfulness, perceived usefulness and confirmation on continuance intention.